Surface Water Hydrology Conditions in Alabio Polder for Irrigation - Soewarno, Soewarno (Universitas Muhammadiyah Surakarta, 1998)
The Alabio polder irrigation which area of 6000 ha is situated at the Negara river basin in Kalimantan Selatan province, consist of agricultural land which major part is approximately used for paddy-fields (60%), swamp zone (30%), and other (10%). During rainy season are usually flooded, which water level of 0,50 â 1,50 m above the ground surface. The flooding is due to the slight slope of the Alabio, Panggang, and Negara river. During field investigatiton period from Desember 1989 to Pebruary 1990, inflow discharge measured in the Tabukan intake was 14,9 â 17,1 m3/det, which water elevation was 2,62 â 2,74 m MSL, in Mahar intake was 0,52 â 2,67 m3/det, which water elevation was 2,94 â 3,25 m MSL. The outflow discharge measured in the Kalumpang drainage main canal was 1,68 â 17,1 m3/det, and in the Luang drainage canal was 13,62 â 16,92 m3/det. The Alabio Polder outside slope was 0,00011 â 0,00025, the inside slope was 0,00002 â 0,00010. The difference of water level elevations for the various discharge in the Alabio canals network is due back water in the downstream Polder area. Sedimentation was accour in the intake and drainage canals. The chemical analyze show that surface water meet to the standard for irrigation. The hydrologycal optimation and water balance study should be necessary.